Effect of inoculating mixed starter cultures of Lactobacillus and Staphylococcus on bacterial communities and volatile flavor in fermented sausages - Yuxin Li; Zhixiang Cao; Zhihui Yu; Yingchun Zhu; Kaile Zhao (Food Science and Human Wellness)
The objective of this study was to explore the effects of the inoculation of mixed starter cultures of Lactobacillus and Staphylococcus (labeled L-S) on microbial community and flavor in fermented sausages during the ripening process. Culture-dependent (colony count) and culture-independent (high-throughput sequencing) methods were employed to evaluate bacterial communities. Volatile compounds were identified by gas chromatography–mass spectrometry, and the results were analyzed by principal component analysis (PCA). The identified bacteria with high relative abundance included Lactobacillus and Pediococcus, and the relative abundances of Leuconostoc and Weissella in fermented sausages were remarkably decreased at the end of the ripening process. At the end of ripening, 2-nonenal, tetradecanal, ethylstearate and terpinyl acetate played substantial roles in the flavor development of the L-S fermented sausages. Sensory evaluation showed a high score in the L-S fermented sausages. Sausages can be inoculated with L-S starter culture to improve the safety and flavor of meat products.